ACUPRESSURE SELF-CARE AS A COMPLEMENTARY THERAPY TO MANAGE HYPERTENSION - Rahmalia Samsara Kristanti; Sandi Alfa Wiga Arsa; Ning Arti Wulandari (Universitas Muhammadiyah Lamongan, 2025)
The Indonesian Tera Klampok gymnastics group has a high prevalence of hypertension. This is evidenced by the results of interviews and preliminary studies as many as 80% of members who suffer from hypertension. This community service aims to increase the knowledge and ability of hypertension patients to apply acupressure independently to control blood pressure to prevent all risks of complications and partners can be independent in checking blood pressure regularly. The implementation of activities includes education, training and assistance for partners in applying acupressure therapy as complementary therapy, the media used are leaflets and power point broadcasts related to acupressure therapy. The participants who attended the activity were 36 people. In the post-test after providing education, training and assistance to partners in applying acupressure therapy as complementary therapy, it showed significant differences in the reduction of systolic and diastolic blood pressure in participants before and after acupressure therapy and there was an increase in knowledge and skills related to hypertension and the benefits of the application of independent acupressure complementary therapy as one of the management of non-pharmacological therapies that can lower blood pressure and partners are able to take part in demonstrations of acupressure techniques and points for hypertension and the community is able to apply acupressure therapy related to hypertension management. Keywords: Hypertension, Acupressure, Health Education, Elderly, Blood Pressure.